Calibration of local earthquake magnitudes in Nepal - Rajaure, S.; Koirala, B. P.; Bhattarai, M.; Maske, S. (Journal of Nepal Geological Society, 2011)
An attempt has been made to calibrate magnitudes of local earthquakes recorded by National Seismological Centre (NSC) of the Department of Mines and Geology (DMG), Nepal with other magnitudes of corresponding earthquakes [eported by International Seismological Centre (ISC), UK, and United States Geological Survey (USGS), USA. Local magnitudes (ML) are used from NSC, corresponding surface wave magnitudes (Ms) and body-wave magnitudes (Mb) are used from catalog of ISC and moment magnitude (Mw) is used from catalog of the USGS. After regression analysis, it has been found that the local magnitude s (ML) reported by NSC are slightly larger than Ms, Mb and Mw in all cases. ML, on average, is larger by an amount of about 0.5, than Ms; with an uncertainty of 0.7. Similarly, ML is larger than corresponding Mb by an amount of about 0.6 and the uncertainty is about 0.5. Likewise, ML is larger than Mw by about 1.0 and the corresponding uncertainty is 0.7.